2013
DOI: 10.1371/journal.pone.0072278
|View full text |Cite
|
Sign up to set email alerts
|

Unique Transcriptional Profile of Sustained Ligand-Activated Preconditioning in Pre- and Post-Ischemic Myocardium

Abstract: BackgroundOpioidergic SLP (sustained ligand-activated preconditioning) induced by 3–5 days of opioid receptor (OR) agonism induces persistent protection against ischemia-reperfusion (I-R) injury in young and aged hearts, and is mechanistically distinct from conventional preconditioning responses. We thus applied unbiased gene-array interrogation to identify molecular effects of SLP in pre- and post-ischemic myocardium.Methodology/Principal FindingsMale C57Bl/6 mice were implanted with 75 mg morphine or placebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 54 publications
(80 reference statements)
0
23
0
Order By: Relevance
“…and CXCL10, and the protective effect of their selective suppression, respectively, have been demonstrated in a number of publications. [57][58][59][60] This also applies for the transcriptional controllers FOS and HMOX1. 57 Several other studies have shown a protective effect of CpG…”
Section: Discussionmentioning
confidence: 99%
“…and CXCL10, and the protective effect of their selective suppression, respectively, have been demonstrated in a number of publications. [57][58][59][60] This also applies for the transcriptional controllers FOS and HMOX1. 57 Several other studies have shown a protective effect of CpG…”
Section: Discussionmentioning
confidence: 99%
“…Tissues were stored at −80 °C in RNAlater (Qiagen, Melbourne, Vic, Australia) immediately following collection, to measure nitric oxide‐regulating genes, Nos1 and Noa1 . RNA extraction, cDNA synthesis and two‐step quantitative real‐time PCR on these tissues were performed as previously described . Quantitative PCR data were normalized to RPL13A (ribosomal protein L13A) and expressed relative to wild‐type controls.…”
Section: Methodsmentioning
confidence: 99%
“…Transcript levels for antioxidant enzymes and determinants of Ca 2ϩ handling and contraction were assessed. RNA extraction, cDNA synthesis, and two-step quantitative real-time PCR was performed as previously described (2) in LV myocardial samples from Gunn and control hearts. Hearts were excised, and LVs were removed, placed in RNAlater solution (Qiagen, Melbourne, VIC, Australia), and frozen at Ϫ80°C.…”
Section: Methodsmentioning
confidence: 99%